Educação, migrações e sociabilidades juvenis bolivianas em São Paulo e Buenos Aires - Dias, Danilo Borges (2018)
The Bolivian youth and its sociability are the aim of this search. It is focused to know how is the school environment among Bolivian students living in São Paulo and Buenos Aires with their hosts. It also concerns to identify how are the sociation and socialization mechanisms built among this youth, their vision about the roles of the school and the education, as well as observe how this relationships between this young people have a new meaning based on their daily experiences, and, lastly, it wonders whether exist or not, observing this two different realities, situations which allow combined statements to both of them. The methodological approach is set on qualitative basis, using the ethnography, group discussion and in-depth interviews. The main theoretical sources are George Simmel, Paul Willis, Pierre Bourdieu and Paulo Freire. Synthetically, the results show that the sociation and socialization among these young Bolivians, initially, happen exclusively by the entrance of the nationality roof, branching, lately, by the varied eligibility of its likes and the relation of this young ones with their environment. The role of the school also shows itself as a variable with many bifurcations, oscillating, with bigger intensity between a persistent disassociation of the topics worked in class and the realities of this young people, passing through some element of preparation for the future until, in a minor proportion, as an element of life and a real function for the present. This search also observed that, even though the young Bolivians from the two cities present a strong inclination to an intra-community way of life, connected to ancestry, they create a new meaning of how to relate with others as they grow and develop themselves with basis on the established links with the receptor society. Finally, it features that there are macro situations which get closer to the realities of São Paulo and Buenos Aires, but it is possible to identify variables which these phenomenons happen in their own way, making impracticable combined statements.